Analisis Risiko Keuangan pada PT Telkom Indonesia Tbk pada Periode 2021-2024 - Febrianti, Feby; Purba, Friska Natalia; Herlina, Dina; Manda, Gusganda Suria (Jurnal Informatika Ekonomi Bisnis, 2025)
Massive digital transformation requires PT Telkom Indonesia Tbk to undertake structural reorganization and diversification of services, especially into the digital sector. While these strategies are necessary to maintain competitiveness, these changes have the consequence of increasing exposure to financial risks, such as liquidity, credit and market risks. This study aims to analyze Telkom's financial risk profile over the 2021-2024 period and assess the effectiveness of the mitigation strategies implemented. Using a descriptive qualitative approach based on literature study and financial statement analysis, this research highlights significant fluctuations in profitability indicators such as EPS and EBIT. Degree of Financial Leverage values that vary between 0.92 to 1.50 reflect the high sensitivity of performance to changes in operating profit, while liquidity ratios such as current ratio and cash ratio show a downward trend in the last three years. Telkom's capital structure also shows moderate dependence on debt, as reflected in the DER and DAR ratios. The results show that although Telkom is on the path of digital transformation, the company still faces challenges in maintaining short-term financial stability and long-term solvency. Therefore, strengthening risk management and operational cost efficiency are key to the sustainability of the business strategy going forward.